(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The study aims at showing the role of tax audit in Impact the quality of tax statements. Tax audit is one of the most important means used by tax management to identify taxable revenues in a just, fair manner. The quality of statements relies on the extent to which the information provided by taxpayers is true and accurate. Tax audit works is compatible with the strategy of increasing tax adherence and detecting non-adherence cases and penalizing those who commit such violations. The study reached a number of results and conclusions. One of the most important results is that tax audit helps improve the information content of the taxpayers tax statements. This leads to recalculating taxable incomes and re-fixing the due tax amount, and consequently raising tax revenues going into the State treasury. Amongst the most notable conclusions is that tax management represents one of the most important users of taxpayers accounting information, as financial reports and statements the main factors contributing to improving financial reporting